2014
DOI: 10.1038/tp.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy mediates neuroplasticity of white matter microstructure in major depression

Abstract: Whether plasticity of white matter (WM) microstructure relates to therapeutic response in major depressive disorder (MDD) remains uncertain. We examined diffusion tensor imaging (DTI) correlates of WM structural connectivity in patients receiving electroconvulsive therapy (ECT), a rapidly acting treatment for severe MDD. Tract-Based Spatial Statistics (TBSS) applied to DTI data (61 directions, 2.5 mm3 voxel size) targeted voxel-level changes in fractional anisotropy (FA), and radial (RD), axial (AD) and mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
86
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 71 publications
13
86
1
1
Order By: Relevance
“…96 This is an interesting finding given evidence that ECT may mediate the neuro plasticity of white matter microstructure in patients with major depression. 103 Furthermore, a recent review has reported that although the mechanisms of its action are still not completely understood, DBS for TRD has shown encouraging therapeutic effects, demonstrating significant and sustained improvements in depressive symptomatology, with remission in a large percentage of cases. 98 To our knowledge, only a limited number of studies of nondrug therapies involving a small patient sample size have been conducted so far.…”
Section: Directions For Future Studiesmentioning
confidence: 99%
“…96 This is an interesting finding given evidence that ECT may mediate the neuro plasticity of white matter microstructure in patients with major depression. 103 Furthermore, a recent review has reported that although the mechanisms of its action are still not completely understood, DBS for TRD has shown encouraging therapeutic effects, demonstrating significant and sustained improvements in depressive symptomatology, with remission in a large percentage of cases. 98 To our knowledge, only a limited number of studies of nondrug therapies involving a small patient sample size have been conducted so far.…”
Section: Directions For Future Studiesmentioning
confidence: 99%
“…is less focal and yet most effective at reducing symptoms of depression, eliciting generalized seizures associated with more widespread neural changes (Perrin et al 2012;Abbott et al 2013;Tendolkar et al 2013;Zhang et al 2013;Dukart et al 2014;Lyden et al 2014;van Waarde et al 2015;Joshi et al 2015). However, the exact nature of network dysfunction responsible for depressive disorders, and how this dysfunction is best targeted by current neurostimulation therapies, remains poorly understood.…”
Section: ]) Electroconvulsive Therapy (Ect)mentioning
confidence: 99%
“…Twenty-four patients returned for the third timepoint; only these patients were used in analyses assessing treatment response, and they received either right unilateral ECT (RUL; n = 18) or a combination of right unilateral and bifrontal ECT (RUL + BF; n = 6) using standard procedures (d'Elia 1970;Zhang et al 2013;Lyden et al 2014), 3 times a week during the index series (mean/SD number of treatments = 11.79/3.34; Table 1) at UCLA Resnick Neuropsychiatric Hospital. A group of healthy never-depressed "control" volunteers were also scanned twice, at baseline and at a 2-to 4-week follow-up, to establish normative values and test-retest reliability of resting-state fMRI variables.…”
Section: Study Visits and Ectmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty seven of the 89 were observational studies (Azuma et al, 2011;Bär et al, 2010;Bayless et al, 2010;Beall et al, 2012;Bersani et al, 2014;Bilgen et al, 2014;Burgese & Bassitt, 2015;Casarotto et al, 2013;Chiaie et al, 2013;Dannlowski et al, 2013;Dukart et al, 2014;Ebert et al, 2010;Galletly, Paterson, & Burton, 2012;Goto et al, 2012;Guloksuz et al, 2015;Hu et al, 2010;Johansson, Ehnvall, Friberg, & Myredal, 2010;Joshi et al, 2015;Kalogerakou et al, 2015;Kautto et al, 2015;Lin et al, 2013;Loo, Mahon, Katalinic, Lyndon, & Hadzi-Pavlovic, 2011;Lucca et al, 2010;Lyden et al, 2014;McCall et al, 2013;Medda et al, 2014;Meeter, Murre, Janssen, Birkenhager, & van den Broek, 2011;Minelli et al, 2014;Nickl-Jockschat et al, 2015;Nordanskog, Larsson, Larsson, & Johanson, 2014;Ota et al, 2015;Oudega et al, 2011;Perrin et al, 2012;Piccinni et al, 2013;Rapinesi et al, 2015;Rapinesi et al, 2013;Royster et al, 2012;Saijo et al, 2010;Samuelsson, Gerdin, Öllinger, & Vrethem, 2012;Tendolkar et al, ...…”
Section: Focus and Design Of The 91 Studiesmentioning
confidence: 99%